The guardian abuses with the fosterer - Jurisprudence study compared to the Kuwaiti Personal Status Law - - Al-hadiah, Muhammad (Jordan Journal of Islamic Studies, 2023)
This research aims to indicate the ruling on the abuse of the guardian in the performance of the rights he is due to the incubator and the concubine. Some saints may be deviant in using the right in a way that does not achieve its purpose, which jurisprudence and law have made in the father's hands the care of the beholder, if it harms the boy, it is an aberration that must be corrected. One of the forms of abuse of the guardian is the injury of the interests of the concubine: from the extraction of official papers to him, or not to the education, if the arbitrariness is established in court; The researcher also addressed the abuse of the guardian in objecting to the provisions of expenses knowing the need of the incubator and those who are in charge of it, and the law dealt with this order with the possibility of the court's discretion in a temporary expense during the consideration of the case.